WHEN VERBS BECOME NOUNS: GRAMMATICAL MBTAPHOR IN STUDENTS' ACADEMIC TEXTS - Refnaldi Refnaldi (Proceedings of ISELT FBS Universitas Negeri Padang, 2015)
The major challenge, according to Systemic Functional Linguistics (SFL), for students in writing courses is the frequent use of grammatical metaphor in acaciemic texts. Grammatical metaphor is the key element of academic discourse and a "single most distinctive characteristic" (Halliday, 2004) of written language compared to spoken language. This study is focused on the use of grammatical metaphors in students' abstracts. Using content analysis as data collection technique, this study examines 20 students' thesis abstract. The findlng shows that the use of grammatical metaphgrs is not yet optimal due to students' lack of understanding of grammatical metaphor functions in written English. The conclusion is there is a need for students on the improvement concerning the use of grammatical metaphors.